Study Of The Pollen Grain Development In Lagenaria siceraria ( Mol.) Standl. infected by Cucumber Green Mottle Mosaic Virus (C.G.M.M.V.). - Pandey, Ravindra Kumar (International Journal of Scientific Research and Management (IJSRM), 2017)
The pollen grain development followed the normal pattern as described for the Angiosperms. The pollen grain development occurs from meiocyte to the mature pollen grain. In the microsporogenesis, the microspore mother cells or the meiocytes underwent meiosis giving rise to the tetrads that were enclosed by the calose. Later, the tetrads were released by the dissolution of the calose by calase activity and microspores underwent mitosis. Microgametogenesis was characterized by asymmetrical mitotic division of each microspore giving rise to bi-nucleate pollen grains. Multivalent and asynchronismas laggard chromosome and chromosome bridges at metaphase 1 and later stage of division were observed more in diseased plants. Pollen viability reduces in diseased plants; sterile pollen may be empty or shrunken. The structures similar to the plastids were found in the cytoplasm and close to the nucleus of the generative cell